Psoriasis drug development and GWAS interpretation through in silico analysis of transcription factor binding sites. Issue 1 (19th March 2015) - Swindell, William R; Sarkar, Mrinal K; Stuart, Philip E; Voorhees, John J; Elder, James T; Johnston, Andrew; Gudjonsson, Johann E
Abstract: Background: Psoriasis is a cytokine‐mediated skin disease that can be treated effectively with immunosuppressive biologic agents. These medications, however, are not equally effective in all patients and are poorly suited for treating mild psoriasis. To develop more targeted therapies, interfering with transcription factor (TF) activity is a promising strategy. Methods: Meta‐analysis was used to identify differentially expressed genes (DEGs) in the lesional skin from psoriasis patients ( n = 237). We compiled a dictionary of 2935 binding sites representing empirically‐determined binding affinities of TFs and unconventional DNA‐binding proteins (uDBPs). This dictionary was screened to identify "psoriasis response elements" (PREs) overrepresented in sequences upstream of psoriasis DEGs. Results: PREs are recognized by IRF1, ISGF3, NF‐kappaB and multiple TFs with helix‐turn‐helix (homeo) or other all‐alpha‐helical (high‐mobility group) DNA‐binding domains. We identified a limited set of DEGs that encode proteins interacting with PRE motifs, including TFs ( GATA3, EHF, FOXM1, SOX5 ) and uDBPs ( AVEN, RBM8A, GPAM, WISP2 ). PREs were prominent within enhancer regions near cytokine‐encoding DEGs ( IL17A, IL19 and IL1B ), suggesting that PREs might be incorporated into complex decoy oligonucleotides (cdODNs). To illustrate this idea, we designed a cdODN to concomitantly target psoriasis‐activated TFs (i.e., FOXM1, ISGF3, IRF1 and NF‐kappaB). Finally, we screened psoriasis‐associated SNPs to identify risk alleles that disrupt or engender PRE motifs. This identified possible sites of allele‐specific TF/uDBP binding and showed that PREs are disproportionately disrupted by psoriasis risk alleles. Conclusions: We identified new TF/uDBP candidates and developed an approach that (i) connects transcriptome informatics to cdODN drug development and (ii) enhances our ability to interpret GWAS findings. Disruption of PRE motifs by psoriasis risk alleles may contribute to disease susceptibility.